A review on the impact of cultural tourism on the sustainability of residents’ livelihood - Zhang, Shiyao; Abdul Aziz, Faziawati; Abu Bakar, Nor Azlina (Human Resource Management Academic Research Society, 2024)
Using the elements of the sustainable livelihood framework, this study aims to identify the impact of cultural tourism practices on residents' livelihoods. Also, this study describes research trends and gaps since 2007. The results showed that cultural tourism generally improved the economic and physical capital of destinations, promoted the development of cultural capital, increased the diversity of local livelihood and was therefore accepted by local participants. However, cultural tourism without proper management may have negative impacts, such as the grabbing and destruction of natural capital and interference with the values and social relations of participants, which may further result in damage to cultural heritages. In recent years, the concern about residents’ capacity building, distribution of benefits, and identity perceptions of local people have become more evident in a lot of studies.